2015
DOI: 10.1785/0120140273
|View full text |Cite
|
Sign up to set email alerts
|

Landslides and Megathrust Splay Faults Captured by the Late Holocene Sediment Record of Eastern Prince William Sound, Alaska

Abstract: We present new marine seismic-reflection profiles and bathymetric maps to characterize Holocene depositional patterns, submarine landslides, and active faults beneath eastern and central Prince William Sound (PWS), Alaska, which is the eastern rupture patch of the 1964 M w 9.2 earthquake. We show evidence that submarine landslides, many of which are likely earthquake triggered, repeatedly released along the southern margin of Orca Bay in eastern PWS. We document motion on reverse faults during the 1964 Great A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The process of ground failure and tsunamigenesis that occurred in Port Valdez is likely similar to events documented throughout the Prince William Sound and Kenai Peninsula region during the 1964 earthquake (Brothers et al, 2016; Finn et al, 2015; Haeussler et al, 2015; Plafker et al, 1969), as well as during some strike‐slip earthquakes in southeast Alaska (Keefer, 1984; Miller, 1960, 1973). Recent geophysical studies have illuminated the locations of submarine landslide debris fields within several coastal fjord settings, characterizing fjord morphology from multibeam bathymetry and subbottom profiling in Port Valdez (Lee et al, 2006, 2007; Parsons et al, 2014; Ryan et al, 2010), Passage Canal near Whittier (Haeussler et al, 2012), Resurrection Bay, near Seward (Haeussler et al, 2007; Lee et al, 2003), and Chenega (Brothers et al, 2016).…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…The process of ground failure and tsunamigenesis that occurred in Port Valdez is likely similar to events documented throughout the Prince William Sound and Kenai Peninsula region during the 1964 earthquake (Brothers et al, 2016; Finn et al, 2015; Haeussler et al, 2015; Plafker et al, 1969), as well as during some strike‐slip earthquakes in southeast Alaska (Keefer, 1984; Miller, 1960, 1973). Recent geophysical studies have illuminated the locations of submarine landslide debris fields within several coastal fjord settings, characterizing fjord morphology from multibeam bathymetry and subbottom profiling in Port Valdez (Lee et al, 2006, 2007; Parsons et al, 2014; Ryan et al, 2010), Passage Canal near Whittier (Haeussler et al, 2012), Resurrection Bay, near Seward (Haeussler et al, 2007; Lee et al, 2003), and Chenega (Brothers et al, 2016).…”
Section: Introductionmentioning
confidence: 63%
“…The process of ground failure and tsunamigenesis that occurred in Port Valdez is likely similar to events documented throughout the Prince William Sound and Kenai Peninsula region during the 1964 earthquake (Brothers et al, 2016;Finn et al, 2015;Haeussler et al, 2015;Plafker et al, 1969), as well as during some strike-slip earthquakes in southeast Alaska (Keefer, 1984;Miller, 1960Miller, , 1973. Recent geophysical studies have illuminated the locations of submarine landslide debris fields within several coastal fjord settings, Plafker et al (1969).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The Lachlan fault in New Zealand shares similar kinematics and slip rates with the SMFS (3.0–6.5 m/ka) and has the potential to produce M w 7.6 to 8 earthquakes with a recurrence time of ~1 ka [ Barnes et al , ]. Several splay faults have been mapped in the Prince Williams Sound, Alaska, at ~150 km from the trench slip with slip rates of ~3.7 m/ka and the potential to produce M w 7–8 earthquakes [ Finn et al , ]. In turn, splay faults located at ~50 km from the trench slip at up to ~9 m/ka [ Liberty et al , ] and earthquakes on these structures have an estimated recurrence time of ~790 years, expecting to be reactivated during most megathrust earthquakes.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, splay faults located at ~50 km from the trench slip at up to ~9 m/ka [ Liberty et al , ] and earthquakes on these structures have an estimated recurrence time of ~790 years, expecting to be reactivated during most megathrust earthquakes. Splay‐fault ruptures in Alaska have been associated with tsunamis [ Liberty et al , ; Finn et al , ; von Huene et al , ]. Liberty et al [] showed that many of these splay faults slipped together during the 1964 Alaska earthquake forming metric scarps on the seafloor and acting as a secondary source for the tsunami.…”
Section: Discussionmentioning
confidence: 99%